An Investigation into the Roots of Violence by African-Americans during Late-Twentieth Century America - AKAKA, Siham; MIHOUBI ,Ahmed (Faculty of Letters and Foreign Languages Department of English, 2018)
In the last decades of the Twentieth Century, American society witnessed an increase in the rate of violence by Africans Americans, which is reflected in the higher rate of crime. Many researchers explained that the increase in violence is related primarily to culture and character of black Americans. Therefore, this dissertation’s main aim is to reveal that the problem of violent crimes committed by African Americans is not a matter of culture as many white Americans believed. In order to achieve this aim, violence was discussed in its historical background as well as a wide range of primary and secondary sources was consulted, especially those sources related to the influence of media on the perception of individuals to real world. In addition, this dissertation discussed different theories, which explain an existing relationship between being subjected to racial discrimination leads African Americans to engage in a world of violent crimes. The analysed data and study findings suggest that roots of violence stem from the distorted image of African Americans portrayed in different American media programs as well as the racially biased educational policies in U.S public schools